Background and distribution of lobar microbleeds in cognitive dysfunction. Issue 11 (16th October 2017) - Matsuyama, Hirofumi; Ii, Yuichiro; Maeda, Masayuki; Umino, Maki; Ueda, Yukito; Tabei, Ken‐ichi; Kida, Hirotaka; Satoh, Masayuki; Shindo, Akihiro; Taniguchi, Akira; Takahashi, Ryosuke; Tomimoto, Hidekazu
Abstract: Objectives: Cerebral microbleeds (CMBs) are often observed in memory clinic patients. It has been generally accepted that deep CMBs (D‐CMBs) result from hypertensive vasculopathy (HV), whereas strictly lobar CMBs (SL‐CMBs) result from cerebral amyloid angiopathy (CAA) which frequently coexists with Alzheimer's disease (AD). Mixed CMBs (M‐CMBs) have been partially attributed to HV and also partially attributed to CAA. The aim of this study was to elucidate the differences between SL‐CMBs and M‐CMBs in terms of clinical features and regional distribution. Materials: We examined 176 sequential patients in our memory clinic for clinical features and CMB location using susceptibility‐weighted images obtained on a 3T‐MRI. The number of lobar CMBs in SL‐CMBs and M‐CMBs was counted in each cerebral lobe and their regional density was adjusted according to the volume of each lobe. Results: Of the total 176 patients, 111 patients (63.1%) had CMBs. Within the patients who had CMBs, M‐CMBs were found in 54 patients (48.6%), followed by SL‐CMBs in 35 (31.5%) and D‐CMBs in 19 (17.1%). The SL‐CMB group showed a significantly higher prevalence of family history of dementia, whereas the M‐CMB group showed an increasing trend toward hypertension and smoking. The prevalence of AD was significantly higher in the SL‐CMBs group, whereas the prevalence of AD with cerebrovascular disease was higher in the M‐CMBs group. The regional density of lobar CMBs was significantly higher in the occipital lobe in the M‐CMB group, whereas the SL‐CMB group showed higher regional density between regions an increasing tendency in the parietal and occipital lobe. Conclusion: The between‐group differences in clinical features and regional distribution indicate there to be an etiological relationship of SL‐CMBs to AD and CAA, and M‐CMBs to both HV and CAA. Abstract : Strictly lobar type had much of dementia family career and high density of CMBs in the occipital and the parietal lobes, these results suggest that strictly lobar CMBs may be due to CAA. Mixed type has much hypertension than strictly lobar type. Lobar CMBs in the mixed type may be partly attributable to CAA.